Espaços confinados: reconhecimento dos riscos característicos para a prevenção de acidentes - Lemos, Paulo Ricardo Matielo (Universidade do Vale do Rio dos Sinos, 2017)
The spaces confined by their constructive characteristics and the geometry that determine their shape, are incompatible with the human permanence in their interior. Throughout history, the construction, cleaning, maintenance and repair activities inside confined spaces have generated numerous accidents and many human losses. One of the main factors generating the losses is the lack of knowledge of the characteristic risks of confined spaces, the main one being the chemical composition of the atmosphere inside it that may be or become incompatible with life. The presence of gases, vapors, and particles that may be toxic, flammable and or that displace oxygen alter the composition of breathable air leading to loss of consciousness and death very quickly. The economic activities in its processes have a wide range of confined areas and environments which requires a consistent dynamic of integrated management of identification, analysis and control of risks in operations in confined spaces
Keywords: Espaço confinado; Permissão de entrada e trabalho; Análise de riscos; Cadastro de espaços confinados; Confined space; Entry and work permission; Risk analysis; Confined space registration